Enhancing longevity of Plasmodium vivax and P. falciparum sporozoites after dissection from mosquito salivary glands. Issue 2 (April 2015) - Lupton, Emily J.; Roth, Alison; Patrapuvich, Rapatbhorn; Maher, Steve P.; Singh, Naresh; Sattabongkot, Jetsumon; Adams, John H.
Abstract: The pre-erythrocytic stages of Plasmodium vivax and Plasmodium falciparum remain challenging for experimental research in part due to limited access to sporozoites. An important factor limiting availability is the laboratory support required for producing infected mosquitoes and the ephemeral nature of isolated extracellular sporozoites. This study was undertaken to investigate methods to improve the availability of this limited resource by extending the longevity of the extracellular sporozoites after mosquito dissection. Our goal in this study was to determine whether buffer conditions more closely mimicking the insect microenvironment could prolong longevity of ex vivo P. vivax and P. falciparum sporozoites. The study compared the current standard dissection buffer RPMI1640 to Hank's Balanced Salt Solution with 1 g/L glucose (HBSS-1) or 2 g/L glucose (HBSS-2) and Grace's Insect Medium for ability to extend longevity of ex vivo P. vivax and P. falciparum sporozoites. The effect of each buffer on sporozoite viability was evaluated by measuring sporozoite gliding motility at 0, 4, 8, and 24 h post-dissection from mosquito salivary glands. Comparisons of mean gliding percentages of ex vivo sporozoites in the different buffers and time points found that RPMI and Grace's both showed strong gliding at 0 h. In contrast, by 4 h post-dissection sporozoites in RPMI consistently had the lowest gliding activity, whereas sporozoites in Grace's had significantly more gliding compared to all other buffers at almost all time points. Our results indicate that P. vivax and P. falciparum sporozoites maintained in insect media rather than the standard dissection buffer RPMI and HBSS retain viability better over time. Graphical abstract: Highlights: Grace's Insect Medium extends longevity of P. vivax and P. falciparum sporozoites. Sporozoites in Grace's Insect Medium stay active longer than those in RPMI or HBSS. Sporozoites in Grace's Insect Medium retain gliding activity for up to ≥ 24 h.